Radiative Mixed Convection over an Isothermal Cone Embedded in a Porous Medium with Variable Permeability - M. F. El-Amin; N. A. Ebrahiem; Amgad Salama; Shuyu Sun (Journal of Applied Mathematics)
The interaction of mixed convection with thermal radiation of an optical dense viscous fluid adjacent to an isothermal cone imbedded in a porous medium with Rosseland diffusion approximation incorporating the variation of permeability and thermal conductivity is numerically investigated. The transformed conservation laws are solved numerically for the case of variable surface temperature conditions. Numerical results are given for the dimensionless temperature profiles and the local Nusselt number for various values of the mixed convection parameter 𝜒, the cone angle parameter 𝑚, the radiation-conduction parameter 𝑅𝑑, and the surface temperature parameter 𝐻.